Increased CD38 expression on T lymphocytes as a marker of HIV dissemination into the central nervous system. Issue 5 (October 2015) - Dentone, Chiara; Fenoglio, Daniela; Schenone, Eva; Cenderello, Giovanni; Prinapori, Roberta; Signori, Alessio; Parodi, Alessia; Kalli, Francesca; Battaglia, Florinda; Feasi, Marcello; Bruzzone, Bianca; Viscoli, Claudio; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Cross-sectional analysis on 20 HIV-1 patients with neurological symptoms admitted to two infectious disease units. Cut-off of HIV–RNA (VL) was 20 copies/ml for plasma and cerebral spinal fluid (CSF). Flow cytometry was used to analyze the phenotype of circulating and CSF T lymphocytes. CD38 mean fluorescence intensity (MFI) was higher on circulating CD4+T lymphocytes from patients with VL >20 copies/ml in plasma (P = 0.001) or CSF (P = 0.001). The frequency of circulating CD8+CD38+T cells and CD38 MFI on these cells were higher in patients with VL >20 copies/ml than in those with undetectable plasma VL (P = 0.030 and P = 0.023). The frequency of CSF CD4+CD38+T, as well as their CD38 and CD95 MFI, were increased in patients with detectable than non-detectable plasma VL (P = 0.01, P = 0.03, and P = 0.05). The % CD38+CD8+T in CSF correlated with time of virological suppression (ρ = − 0.462, P = 0.040) and the CNS penetration-effectiveness (CPE) score (ρ = − 0.467, P = 0.038). In conclusion, (a) the expression of CD38+ on both CD4+, CD8+T lymphocytes from peripheral blood and CSF discriminated between viremic and non-viremic patients and (b) T cell activation/apoptosis markers inversely correlated with CPE to remark the importance for therapy to restore immunological functions.